Analyzing the Effect of Cyber Security on FinTech Variables (Evidence from Jordanian Banks) - Nussir, Nour Ali; Eid, Ali Ibrahim Abu; Alraqqad, Rasha Mohammad Rath’an; Alsukhni, Emad; Baqader, Saleh Mohammed; Alataibi, Mahmud; Hariri, Mohammad; Alabdullatif, Sultan Abdullah; Bazhair, Ayman Hassan; Jahmani, Ashraf (Journal of Posthumanism, 2025)
The current study aiming at finding out the extent of awareness of the importance of cyber security among dealers using financial technology instruments and the role played by technology infrastructures. A questionnaire was employed to study this association. 370 questionnaires were issued to employees at three Jordanian banks, ranging from the frontline to the management level. It was shown that there is a statistically significant connection between the utilization of Fintech tools and cyber security.